Strong coupling of optical modes in photonic molecules with CdTe nanocrystals - DONEGAN, JOHN FRANCIS; RAKOVICH, YURY (My University, 2005)
We present a detailed study of the localized coupled-cavity modes in a photonic molecule formed from two dielectric spherical microcavities with CdTe nanocrystals. A layer-by-layer deposition technique provides controllable coating of the microspheres with a shell of close-packed nanocrystals of approximately 4 nm in diameter. The observed spectral structures originate from the coupling of the electronic transitions in nanocrystals and the photon states of interacting microspheres and, in analogy to the formation of molecular electronic orbits, can be assigned to bonding and antibonding photon localized states. Keywords: coupled microcavities, semiconductor nanocrystals, whispering gallery modes, mode degeneracy
PUBLISHED
Keywords: coupled microcavities; semiconductor nanocrystals